2017
DOI: 10.1016/j.drugalcdep.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents, alcohol, and marijuana: Context characteristics and problems associated with simultaneous use

Abstract: We investigated contexts of simultaneous use of alcohol and marijuana and the impact of simultaneous use on problems among adolescents. Ecological momentary assessment data were obtained over two weekends from 150 adolescents in California (47% female, M age = 16.36 years), using smartphone surveys administered early and late in the evening and again the following morning. We assessed whether, in what context, and with whom adolescents drank alcohol and used other substances over 3 evening hours. We assessed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 28 publications
15
94
0
Order By: Relevance
“…Our results indicate that when a responsible adult is present throughout a social gathering, the risk of alcohol consumption among underage drinkers is lower, a finding that held across models when comparing heavy drinkers to those who consume less than binge levels. While this result confirms research indicating a protective effect of adult supervision for girls (Bersamin et al., ), it contradicts other research demonstrating little or no effects of adult supervision on youth alcohol use (e.g., Lipperman‐Kreda et al., ). Mere presence of an adult may not be sufficient to deter alcohol consumption, particularly if that adult is not aware that alcohol is present.…”
Section: Discussionsupporting
confidence: 66%
“…Our results indicate that when a responsible adult is present throughout a social gathering, the risk of alcohol consumption among underage drinkers is lower, a finding that held across models when comparing heavy drinkers to those who consume less than binge levels. While this result confirms research indicating a protective effect of adult supervision for girls (Bersamin et al., ), it contradicts other research demonstrating little or no effects of adult supervision on youth alcohol use (e.g., Lipperman‐Kreda et al., ). Mere presence of an adult may not be sufficient to deter alcohol consumption, particularly if that adult is not aware that alcohol is present.…”
Section: Discussionsupporting
confidence: 66%
“…However, prior work (Mallett et al, ) has found that students who combined alcohol with marijuana and/or other substances had increased negative consequences compared to students who only used alcohol. With an adolescent sample, Lipperman‐Kreda and colleagues () found occasions with SAM use were associated with a 110% increase in number of negative behavioral consequences (e.g., driving after drinking, getting into a verbal argument or physical fight) compared to occasions with no substance use, and this was largely associated with increased alcohol consumed on those occasions.…”
Section: Sam Use and Consequences Among Young Adultsmentioning
confidence: 99%
“…We hypothesized that days with SAM use would be associated with greater alcohol use compared to alcoholonly days and that SAM use would be associated with greater reports of perceived positive and negative alcohol-related effects or consequences. Based on findings from prior studies (e.g., Lipperman-Kreda et al, 2017;Mallett et al, 2019), we further hypothesized that greater alcohol use on SAM occasions may account for the effects of SAM use on alcohol-related consequences.…”
Section: Present Studymentioning
confidence: 99%
“…Simultaneous alcohol and marijuana (SAM) use can have more serious negative consequences than using either substance alone (for a review, see Yurasek et al., ). These include driving under the influence and having alcohol‐related accidents (Arterberry et al., ; Chihuri et al., ; Lipperman‐Kreda et al., ; Terry‐McElrath et al., ), cognitive impairment (Mallett et al., ), and substance use disorder symptomatology (Agrawal et al., ; Mallett et al., ; Midanik et al., ; Subbaraman and Kerr, ). The majority of individuals who use alcohol and marijuana engage in SAM use on at least some occasions (Agrawal et al., ; Brière et al., ; Collins et al., ; Midanik et al., ; Pape et al., ; Subbaraman and Kerr, ).…”
Section: Normative Influences On Substance Usementioning
confidence: 99%